The Role of Counseling in Changing Attitudes of First-Trimester Pregnant Women in Preventing Anemia Post-Health Crisis at Sudiang Raya Community Health Center, Makassar (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Anemia is one of the most common nutritional problems affecting pregnant women worldwide and remains a major public health concern, particularly in developing countries. It poses significant risks to both maternal and fetal health, potentially leading to complications such as preterm birth, low birth weight, and increased maternal mortality. Several factors contribute to the development of anemia during pregnancy, including inadequate iron intake, excessive blood loss, vitamin B12 and folic acid deficiencies, and chronic diseases. According to the World Health Organization (WHO) in 2023, approximately 78% of pregnant women globally experience anemia, highlighting the urgent need for effective prevention strategies. Counseling has been recognized as an important intervention to enhance maternal knowledge, attitudes, and behaviors related to anemia prevention. This study aimed to determine whether counseling has an effect on changes in the attitudes and behaviors of pregnant women in preventing anemia at Sudiang Raya Community Health Center, Makassar, in 2024. The research employed an observational analytical method with a descriptive approach, using an accidental sampling technique to select 40 pregnant women as respondents. Data collection was conducted through structured interviews using a validated questionnaire, and statistical analysis was performed to assess the relationship between counseling and changes in attitude and behavior. The results revealed a significant effect of counseling on improving the attitudes and behaviors of pregnant women regarding anemia prevention, with a p-value of 0.001, indicating a strong statistical association. This suggests that structured counseling sessions focusing on the importance of nutrition, supplementation, and healthy lifestyle practices can effectively influence pregnant women’s readiness to prevent anemia. Based on these findings, it is recommended that community health centers intensify counseling programs and integrate them into routine antenatal care to reduce anemia prevalence and improve pregnancy outcomes.